Single-Stranded Oligonucleotide-Mediated Inhibition of Respiratory Syncytial Virus Infection - Pålsson, Sandra Axberg; Dondalska, Aleksandra; Bergenstråhle, Joseph; Rolfes, Caroline; Björk, Albin; Sedano, Laura; Power, Ultan F.; Rameix-Welti, Marie-Anne; Lundeberg, Joakim; Wahren-Herlenius, Marie; Mastrangelo, Peter; Eleouet, Jean-Francois; et al. (Frontiers in Immunology, 2020)
Respiratory syncytial virus (RSV) is the leading cause of acute lower respiratory tract infections in young children. Currently, there is no RSV vaccine or universally accessible antiviral treatment available. Addressing the urgent need for new antiviral agents, we have investigated the capacity of a non-coding single-stranded oligonucleotide (ssON) to inhibit RSV infection. By utilizing a GFP-expressing RSV, we demonstrate that the ssON significantly reduced the proportion of RSV infected A549 cells (lung epithelial cells). Furthermore, we show that ssON´s antiviral activity was length dependent and that both RNA and DNA of this class of oligonucleotides have antiviral activity. We reveal that ssON inhibited RSV infection by competing with the virus for binding to the cellular receptor nucleolin in vitro. Additionally, using a recombinant RSV that expresses luciferase we show that ssON effectively blocked RSV infection in mice. Treatment with ssON in vivo resulted in the upregulation of RSV-induced interferon stimulated genes (ISGs) such as Stat1, Stat2, Cxcl10 and Ccl2. This study highlights the possibility of using oligonucleotides as therapeutic agents against RSV infection. We demonstrate that the mechanism of action of ssON is the inhibition of viral entry in vitro, likely through the binding of the receptor, nucleolin and that ssON treatment against RSV infection in vivo additionally results in the upregulation of ISGs.